THE IMPACT OF ARTIFICIAL INTELLIGENCE ON MARKETING PERFORMANCE IN INDUSTRIAL COMPANIES - Feras. W. Aldoori; Ahmed Frikha (Scholars Digest Publishing, 2024)
This study aims to explore the impact of artificial intelligence on marketing performance in Iraq. Industrial facilities in Iraq were chosen as the research field, while the community consisted of employees in these facilities, estimated at 2000 employees. A sample of 500 workers was drawn. The researcher adopted a descriptive-analytical approach in this study as it suits the research topic. The researcher also designed a questionnaire as a research tool. The research concluded a number of important findings, including: - The existence of a significant effect between the dimensions of artificial intelligence and marketing performance. The researcher recommended the necessity of enhancing the reliance on smart technology and AI in industrial companies to boost marketing performance.
Keywords: Artificial intelligence, smart technology, marketing performance, industrial companies.